Preventing Stunting in Adolescents Through Religious-Based Peer Guidance - Asroful Kadafi; Noviyanti Kartika Dewi; Silvia Yula Wardani; Nur Kholifah; Cindi Febi Fatmawati (Universitas PGRI Yogyakarta, 2026)
Stunting remains a critical nutritional challenge in Indonesia, contributing to long-term cognitive, economic, and health deficits. This study aimed to evaluate the effectiveness of religious-based peer guidance in improving adolescents' understanding of stunting as a preventive strategy. A quasi-experimental design with a non-equivalent control group was employed. The sample consisted of 20 adolescents with low baseline knowledge of stunting, divided equally into an experimental group (receiving religious-based peer guidance) and a control group (receiving conventional peer guidance through discussion only). The stunting understanding scale, developed based on Bloom's Taxonomy, was administered as a pre-test and post-test. Data were analyzed using the Wilcoxon Signed-Rank Test and the Mann-Whitney U Test. Results indicated that both groups showed significant improvements; however, the experimental group demonstrated a substantially greater increase, moving from moderate to high understanding levels (post-test scores of 90–120), while the control group remained in the moderate range (post-test scores of 60–89). The Mann-Whitney U Test revealed a significant difference between the two groups (p = 0.000), confirming the superior effectiveness of the religious-based approach. These findings suggest that integrating religious values into peer guidance not only enhances cognitive understanding but also reinforces adolescents' internal commitment to stunting prevention. This study contributes a novel, culturally grounded intervention model for counselors and health educators. Keywords: adolescent health, Peer guidance, quasi-experimental study, religious values, stunting prevention